The effectiveness of a health promotion program using the International Organization for Standardization in Klongyong and Nikhompattana, Thailand - SUCHINDA JARUPAT MARUO; Piasue, Noppawan; Kalampakorn, Surintorn; Utthiya, Pinyo; Sasimonthonkul, Siriporn; Tabuchi, Hisaaki; Akasaki, Hisaki; Watanabe, Toshiaki; Taki, Naoya; UCHIYAMA, RYOJI; et al. (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Aim: This study aimed to appropriately establish a healthcare program in Thailand that acquired ISO 9001 certification; QC14J0022 (the International Organization for Standardization, ISO) improved problems and inspected the program’s effectiveness. Furthermore, we are making this ISO health promotion widely available in Asian countries and are making an international contribution. Method: We implemented a 9-month health program in Klongyong and a 6-month health program in Nikhompattana, Rayong, Thailand. This program assessed findings from pedometry, anthropometry, physical fitness, and brain function tests. Results: In Klongyong, the average number of walking and exercise steps was 3471.3, and in Nikhompattana, the average number of walking and exercise steps was 4695.5. The pre- and post-health program results in Klongyong showed significant differences in blood pressure, hand grip strength, the 10-meter obstacle walk and the 6-minute walk. In Nikhompattana, there were significant differences in hand grip strength and sit-and-reach flexibility as well as the brain function tests. The pre- and post-health program results in Klongyong and Nikhompattana showed significant differences in the total number of “forgets”. Conclusions: The findings from before and after the health program in Nikhompattana suggest that the increased physical activity during the course of the program may have led to improved brain function results.